Experimental cryptosporidiosis in kids - Koudela, B; Jirí, V (Veterinary parasitology, 1997)
The clinical, pathological and parasitological features of cryptosporidiosis resulting from experimental inoculation with 6 x 10(6) Cryptosporidium parvum oocysts were studied in kids. Decreased appetite and depression became apparent 72 h post inoculation. Subsequently watery feces with clumps of mucus and color changes from brown to yellow were observed. The mean duration of diarrhea was 4.2 days. Oocyst shedding started 4 days post inoculation (DPI), started to decrease at 7 DPI, and lasted until 12 DPI. The evidence of high infectivity and fast transmission of C. parvum oocysts was observed under standard zoohygienic conditions. The characteristics of intestinal lesions were similar to those found in other neonatal ruminants infected with C. parvum. The most severe lesions were seen in the posterior jejunum and ileum from 3 to 7 DPI, characterized by villus atrophy, villus blunting, fusion of atrophic villi, crypt hyperplasia, inflammatory infiltration in the lamina propria, and metaplasia of mucosal epithelium. Scanning electron microscopy of ileal epithelium revealed ultrastructural changes on the surface of intestinal mucosa. No cryptosporidia or associated pathological lesions were found in the large intestine or other tissues. The distribution of cryptosporidia in the intestine and number of cryptosporidia per ileal villus on different DPI were also estimated for detailed characterization of the infection in kids as a model for experimental cryptosporidiosis.
Keywords: průjem; Microvilli; ileum; mikroklky; feces; Cryptosporidiosis; kryptosporidióza; kozy; střevní sliznice; Diarrhea; nemoci koz; Goat Diseases; zvířata; chuť k jídlu; Feces; Cryptosporidium parvum; Goats; Appetite; Depression; Animals; Ileum; deprese; Intestinal Mucosa